Characteristics of Adults With Diagnosed HIV Who Experienced Housing Instability: Findings From the Centers for Disease Control and Prevention Medical Monitoring Project, United States, 2018. (22nd May 2022) - Marcus, Ruthanne; Tie, Yunfeng; Dasgupta, Sharoda; Beer, Linda; Padilla, Mabel; Fagan, Jennifer; Prejean, Joseph
Abstract: People living with HIV (PLWH) who experience homelessness have poorer clinical outcomes than people with HIV who are not homeless; however, there is limited information on PLWH who experience other forms of housing instability. We used interviews and medical record abstraction data from the Medical Monitoring Project, collected 2018–2019 ( N = 4, 050), to describe sociodemographic characteristics and clinical outcomes of adults with HIV by whether people experienced unstable housing in the past 12 months. Overall, 21% were unstably housed, of which 55.2% were unstably housed but not homeless. People who were unstably housed were more likely to be younger, have lower educational attainment, be previously incarcerated, live at or below the poverty level, and have poorer mental health and clinical outcomes, independent of homelessness. Interventions to address housing instability, integrated with clinical care, could benefit not just PLWH who are homeless but also those who are unstably housed.